2022
DOI: 10.1186/s12957-022-02732-w
|View full text |Cite
|
Sign up to set email alerts
|

A case study of combined neoadjuvant chemotherapy and neoadjuvant immunotherapy in resectable locally advanced esophageal cancer

Abstract: Background The prognosis of patients under existing neoadjuvant chemotherapy or neoadjuvant chemoradiotherapy requires improvement. Whereas programmed cell death 1 (PD-1) inhibitors have shown promising response in advanced esophageal cancer, they have not been used in the perioperative treatment of resectable locally advanced esophageal cancer. Whether immunotherapy can be incorporated into neoadjuvant therapy has became a challenging question for researchers. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…By retrospectively analyzing clinical data from patients with borderline resectable PDAC who underwent NACT followed by LPD or OPD (20 cases vs 57 cases) at Fudan University Shanghai Cancer Center between January 2020 and December 2022, we found that despite a longer median operative time (419 vs. 325 min, P < 0.001), the LPD group had a signi cantly lower Clavien-Dindo complication rate (35.0% vs 66.7%, P = 0.018). There were no signi cant differences between the two groups in the number of retrieved lymph nodes, R1 resection rate, median postoperative length of stay, recurrence-free survival (RFS), and OS [20]. All 20 patients in the LPD group underwent successful operations without conversion to open surgery.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…By retrospectively analyzing clinical data from patients with borderline resectable PDAC who underwent NACT followed by LPD or OPD (20 cases vs 57 cases) at Fudan University Shanghai Cancer Center between January 2020 and December 2022, we found that despite a longer median operative time (419 vs. 325 min, P < 0.001), the LPD group had a signi cantly lower Clavien-Dindo complication rate (35.0% vs 66.7%, P = 0.018). There were no signi cant differences between the two groups in the number of retrieved lymph nodes, R1 resection rate, median postoperative length of stay, recurrence-free survival (RFS), and OS [20]. All 20 patients in the LPD group underwent successful operations without conversion to open surgery.…”
Section: Discussionmentioning
confidence: 98%
“…The sample size is calculated based on the Clavien-Dindo complication rate. According to the retrospective study experience of our center, the incidence of Clavien-Dindo complications of open pancreaticoduodenectomy is 66.7%, and that of laparoscopic pancreaticoduodenectomy is 35.0% [20]. The sample size was calculated using the Tests for Two Proportions module of software PASS 2015 (NCSS, LLC, 329 North 1000 East Kaysville, Utah 84037).…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation